1984
DOI: 10.2172/5070697
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of mutagens in solvent-refined coal liquids

Abstract: SUMMARYThe purpose of this investigation was to evaluate any changes in the chemical composition and microbial mutagenicities of two representative solventrefined coal (SRC) liquids as a function of exposure time to sunlight and air. This information was desired to assess potential health hazards arising from ground spills of these liquids during production, transport and use. Results of microbial mutagenicity assays using Salmonella typhimurium TA98, conducted after exposure, showed that the mutagenicities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…(The 14,000-ppm concentration of 6-aminochrysene [6-AC] in sample #2515-012-03 is believed to be a large contaminant that carried into this fraction.) These reductions in amino-PAH concentrations are consistent with the results of laboratory studies by Kalkwarf et. al.…”
Section: Quantitative Analysis Of Npac In Selected Samplessupporting
confidence: 91%
See 2 more Smart Citations
“…(The 14,000-ppm concentration of 6-aminochrysene [6-AC] in sample #2515-012-03 is believed to be a large contaminant that carried into this fraction.) These reductions in amino-PAH concentrations are consistent with the results of laboratory studies by Kalkwarf et. al.…”
Section: Quantitative Analysis Of Npac In Selected Samplessupporting
confidence: 91%
“…The amino-PAH have been previously identified as the most mutagenic compounds found in coal-deri ved materials (Wilson et al, 1980;Guerin et al, 1980). The data are also in agreement with that of WCW1-319A aRepresents solvent-soluble portions, as previously described Kalkwarf et al (1984), Wright and Weimer (1984) and , who demonstrated that exposure of coal liquids to air and/or sunlight eliminated or greatly reduced the microbial mutagenicity of the materials. The data from these workers, along with the data for these three samples, would suggest that any of the site samples that had been exposed to environmental conditions would likely have low mutagenic activity as a result of the decreased amino-PAH content.…”
Section: Microbial Mutagenicitysupporting
confidence: 91%
See 1 more Smart Citation